Pengaruh Kualitas Pelayanan dan Fasilitas Kesehatan Terhadap Kepuasan Pasien BPJS Pada RSU Mina Padi Kabupaten Simalungun - Marisi Butarbutar; Loist Abdi Putra; Musa Fernando Silaen; Arrum Yolandra Yolandra; Efendi Efendi (Program Pascasarjana (S2-Ilmu Manajemen) Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2022)
Objective. The purposes of this research are: 1) To describe the quality of service, health facilities and satisfaction of BPJS patients at Mina Padi General Hospital, Simalungun Regency. 2) To determine the effect of service quality and health facilities on BPJS patient satisfaction at Mina Padi General Hospital, Simalungun Regency, either simultaneously or partially. Research Methods. The research design used in this research is library research and field research. Data collection techniques used in this research are questionnaire method, interview method and documentation method. Results. The results of the study can be concluded as follows: Service quality, health facilities are good, and patient satisfaction is also categorized as good. The results of the regression analysis are = 7.407 + 0.378 X1 + 0.364 X2, meaning that the quality of services and health facilities has a positive and significant effect on patient satisfaction. 3) The results of the correlation analysis obtained a value of r = 0.794, meaning that there is a strong and positive relationship between the quality of services and health facilities and patient satisfaction. The value of the coefficient of determination R = 0.631 means that the level of patient satisfaction can be explained by the quality of services and health facilities of 63.1%. The research hypothesis H0 is rejected, meaning that the quality of services and health facilities has a positive and significant effect on BPJS patient satisfaction at Mina Hospital in Simalungun Regency, either simultaneously or partially. Conclusion. To create a good quality of service, Mina Padi General Hospital in Simalungun Regency should increase the number of inpatient rooms so that sick patients can be treated immediately and receive incentive treatment from medical personnel. To improve health facilities at Mina Padi General Hospital, Simalungun Regency, it is better to increase the number of specialist doctors so that patients who need treatment can be handled immediately. And so that patients feel comfortable, the hospital should be able to overcome the smell of waste. To create patient satisfaction, it is recommended that Mina Padi Hospital, Simalungun Regency, need to increase the supply of medicines needed by BPJS patients.